2017
DOI: 10.3389/fncel.2017.00312
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Human Umbilical Cord Mesenchymal Stem Cells on Glioblastoma Stem Cells by Direct Cell Interaction or Via Released Soluble Factors

Abstract: Glioblastoma (GBM), the most common primary brain tumor in adults, is an aggressive, fast-growing and highly vascularized tumor, characterized by extensive invasiveness and local recurrence. In GBM and other malignancies, cancer stem cells (CSCs) are believed to drive invasive tumor growth and recurrence, being responsible for radio- and chemo-therapy resistance. Mesenchymal stem cells (MSCs) are multipotent progenitors that exhibit tropism for tumor microenvironment mediated by cytokines, chemokines and growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 61 publications
5
56
2
1
Order By: Relevance
“…UC-MSCs exhibit typically fibroblast-like morphology ( Fig. 1a) and flow cytometry analysis of surface marker expression revealed that these cells express high levels of CD 34, CD44, CD45, CD73, CD90, CD54, CD105, HLA-DR (Table 1), which is consistent with the characteristics of UC-MSCs that have been reported (32). UC-MSC has the potential to differentiate into osteogenic, adipogenic or chondrogenic in vitro under appropriate induction conditions.…”
Section: Characterization Of Huc-mscssupporting
confidence: 84%
“…UC-MSCs exhibit typically fibroblast-like morphology ( Fig. 1a) and flow cytometry analysis of surface marker expression revealed that these cells express high levels of CD 34, CD44, CD45, CD73, CD90, CD54, CD105, HLA-DR (Table 1), which is consistent with the characteristics of UC-MSCs that have been reported (32). UC-MSC has the potential to differentiate into osteogenic, adipogenic or chondrogenic in vitro under appropriate induction conditions.…”
Section: Characterization Of Huc-mscssupporting
confidence: 84%
“…Accumulating evidences indicate that the cross-talk between MSCs and tumor cells results in both pro-tumor and antitumor effects, raising safety concerns for clinical application in oncology (Barkholt et al, 2013) (Figure 3). The discrepancies in the ability of MSCs to promote or suppress tumor development may be attributable to differences in experimental tumor models, MSC tissue source, dose or timing of the MSC treatment, cell delivery method, control group chosen, and other experimental conditions (Bortolotti et al, 2015;Bajetto et al, 2017). In this regard, a study demonstrated that direct (cell-to-cell contact) or indirect (released soluble factors) interaction between umbilical cord MSCs and glioblastoma stem cells produces divergent effects on cell growth, invasion and migration (Bajetto et al, 2017).…”
Section: Divergent Roles Of Mscs In Cancer Treatmentmentioning
confidence: 99%
“…The discrepancies in the ability of MSCs to promote or suppress tumor development may be attributable to differences in experimental tumor models, MSC tissue source, dose or timing of the MSC treatment, cell delivery method, control group chosen, and other experimental conditions (Bortolotti et al, 2015;Bajetto et al, 2017). In this regard, a study demonstrated that direct (cell-to-cell contact) or indirect (released soluble factors) interaction between umbilical cord MSCs and glioblastoma stem cells produces divergent effects on cell growth, invasion and migration (Bajetto et al, 2017). Additionally, the application of MSCs for cancer patients is a more complex situation in which other factors have to be taken into consideration.…”
Section: Divergent Roles Of Mscs In Cancer Treatmentmentioning
confidence: 99%
“…Another interesting finding was the contrasting effect observed by Bajetto et al (2017) regarding direct cell-cell contact and secretome-mediated effects [79]. Human UC-MSCs cultured in direct contact with GBM CSCs inhibited their proliferation, while the factors secreted by UC-MSCs increased CSCs proliferation rate through transient ERK1/2 and Akt phosphorylation/activation.…”
Section: Mscs Secretome and Gliomasmentioning
confidence: 99%
“…Among those factors IL8, CXCL1, CXCL5 and IL6 were present. In addition, activation of the CXC chemokine receptor 2 (expressed in GBM cells) seems to be crucial for the effects observed [79].…”
Section: Mscs Secretome and Gliomasmentioning
confidence: 99%